Association of parental stress and early childhood caries - Seyed Ebrahim Jabbarifar; Neda Ahmady; Seyed Ahmad Reza Sahafian; Fatemeh Samei; Shima Soheillipour (Wolters Kluwer Medknow Publications, 2009)
Background:Little research has been carried out on whether the parental stress affects children's oral health in general and dental caries in particular. This study aimed to investigate the association be-tween parental stress and early childhood caries (ECC). Methods: A cross-sectional study was designed that included 250 children of 4-6 year-old; 127 ones attended the pediatric department of Isfahan School of Dentistry who had early childhood caries and a comparison group of 123 caries free children attended five kindergartens and pre-schools in Isfahan city. Clinical examinations were conducted to evaluate the caries status. The parents of the two study groups completed the self-administrated long form of the Parenting Stress Index questionnaire. De-tails of their socio-demographic status were gathered too. The collected data were analyzed by SPSS version 11.5. The nonparametric Mantel-Haenszel test for correlation statistics was used to determine bivariate associations between total parenting stress and their domains scores in the two groups; i.e., those with early childhood caries and the caries free group. Results: Mean score of PSI in the early childhood caries and caries free group were 286.66 ± 66.26 and 273.87 ± 31.03, respectively. There was not any significant relationship between total parental stress and ECC. The scores of the following domains of PSI demonstrated significant differences between ECC and CF groups: child reinforcement, child distractibility, child deficit attention, life stress and relationship with spouse (P = 0.01, 0.01, 0.001, 0.005 respectively). Conclusion: Findings of this study did not show any significant association between total parenting stress score and prevalence of early childhood caries.